Pola Komunikasi Pemerintahan Kabupaten Kulon Progo dalam Meningkatkan Pendapatan Asli Daerah Tahun 2014-2018 - sarmito mito; Dyah Mutiarin; Achmad Nurmandi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
This study aims to determine how the communication patterns carried out by the government of Kulon Progo to increase local revenue (PAD). This research uses descriptive qualitative method, how many indicators in this study were analyzed using Nvivo 12 Plus software. Data collection is done through observation, interview, and documentation. This research was conducted in Kulon Progo Regency, Provision of the Special Region of Yogyakarta, involving the Regent, TAPD, BAPPEDA, BKAD, and DPRD. The results of this study show a positive trend in increasing PAD kulon progo from the period 2014-2018. Good communication is carried out by the Kulon Progo government to increase PAD, by conducting internal and external communication. Internal communication between institutions that are leading sectors in the effort to increase PAD, and external communication with the community to form a joint commitment to the success of efforts to increase PAD, and with the private sector through a Memorandum of Understanding (MoU), this is done as a means and supporting infrastructure in efforts to increase PAD.